Japan's carnival war : mass culture on the home front, 1937-1945 - Uchiyama, Benjamin, 1979- (Cambridge University Press, 2020)
"This book is about the evolution of mass culture into what I term "carnival war" in Japan, reorienting our perspectives on daily life between 1937 and 1945. Although the Asia-Pacific War created the opportunity for the state to expand its control over society, it also fractured Japanese people's sense of identity, which spilled out through a cultural framework which, this book will argue, is best understood as carnival war. Carnival war encompassed both "official" cultural practices shining in the spotlight and "unofficial" cultural practices lurking in the shadows. It requires thinking not only about the activities of official purveyors of entertainment like Kinoshita Circus, but also the "ghetto" circus, the half-man, half-dog circus freaks who echoed, mocked, and inverted the pristine, official national culture the wartime state was trying to build. Second, a study of carnival war examines the unevenness of state attempts to mobilize society for war; the dynamic, improvisational dimension to total war mobilization"--